The Interplay Between Imla’ Mastery and Writing Errors in Maharah Kitabah: A Case Study at Junior High School - Laila Nailil Ighfariyah; Saefullah Azhari; Nurul Istiqomah (Sekolah Tinggi Agama Islam Darul Ulum Banyuanyar Pamekasan, 2025)
This study investigates the difficulties faced by junior high school students in developing maharah kitabah (writing skills) within Arabic language learning, focusing on errors from the perspective of imla’ (Arabic orthography). The problem arises from students’ limited exposure to Arabic in their previous learning environments, which impacts their ability to write correctly and fluently. Common challenges identified include difficulties in mastering Arabic letters, vocabulary limitations, grammatical errors, and incorrect connections between letters. To address these issues, effective learning strategies and environmental support—particularly from parents—are crucial. The research employs a qualitative descriptive approach consisting of four stages: data collection, data reduction, data presentation, and conclusion drawing. The participants were students of Madrasah Tsanawiyah Taswirul Afkar Surabaya. The findings indicate that the majority of students demonstrate fairly good writing proficiency; however, a small proportion still struggle with specific imla’ aspects, particularly in writing the hamzah and in adding or omitting letters unintentionally. The study contributes to understanding the relationship between imla’ mastery and Arabic writing performance, emphasizing the importance of integrating orthographic awareness in Arabic writing instruction. These insights can guide educators in designing more effective pedagogical approaches to improve maharah kitabah among learners of Arabic at the junior high school level.